Intraorganizational Ecology of Strategy Making and Organizational Adaptation: Theory and Field Research - Burgelman, Robert A. (Organization Science, 1991)
This paper presents an intraorganizational ecological perspective on strategy making, and examines how internal selection may combine with external selection to explain organizational change and survival. The perspective serves to illuminate data from a field study of the evolution of Intel Corporation's corporate strategy. The data, in turn, are used to refine and deepen the conceptual framework. Relationships between induced and autonomous strategic processes and four modes of organizational adaptation are discussed. Apparent paradoxes associated with structural inertia and strategic reorientation arguments are elucidated and several new propositions derived. The paper proposes that consistently successful organizations are characterized by top managements who spend efforts on building the induced and autonomous strategic processes, as well as concerning themselves with the content of strategy; that such organizations simultaneously exercise induced and autonomous processes; and that successful reorientations in organizations are likely to have been preceded by internal experimentation and selection processes effected through the autonomous process.